Prevalence and determinants of vitamin D deficiency amongst patients in Erbil, Kurdistan region of Iraq - Shwan Othman Ameen; Banan Qasim Rasool; Aya Nasih Mohammad; Sayran Mohamad Tahr; Gazang Noori Abdulla; Dhuha Abdulraheem Omar; Anna Závadová; Bareq Sabeeh Hashim (National Scientific Medical Center, 2023)
Aim: This study aims at calculating the prevalence of Serum Vitamin D deficiency and determining risk factors associated with deficiency amongst patients in Erbil, Kurdistan Region of Iraq. Material and methods: This was a prospective cross-sectional study conducted on 424 patients from September to November 2021 in the Outpatient Department of Kurdistan Cardiac Center - Surgical Specialty hospital. Results: Results showed that study population consisted of adults aged 30 years and above, 171 (40.3%) females and 253 (59.7%) males. The majority of the study population (51.9%) were Serum Vitamin D deficient, 27.6% were Serum Vitamin D insufficient and 20.5% had normal Vitamin D levels. Serum Vitamin D deficiency was seen more frequently among female gender, increased BMI, previous infection of COVID 19, Diabetes Mellitus and those with abnormal lipid profiles. Conclusion: There is a high prevalence of Serum Vitamin D deficiency in Erbil, Kurdistan Region of Iraq. In addition, there were associations between Serum Vitamin D deficiency and many other diseases. Therefore, medical practitioners should consider more education of patients regarding importance of vitamin D status in the body.